Increasing Social Integration in an Interdisciplinary MA Programme through Group Work - Elming, Jakob (Improving University Science Teaching and Learning, 2023)
In an interdisciplinary MA programme, it is especially important that the students get socially integrated from the beginning. Most often not only the place and people will be new but also the field of study. This can be difficult to handle without a network. In this project I will investigate using group work to help initiate social integration. In this context, I will also reflect on the different group work I conducted.